Bortezomib with dexamethasone as first-line treatment for AL amyloidosis with renal involvement. (2nd January 2016) - Huang, Xianghua; Wang, Qingwen; Chen, Wencui; Ren, Guisheng; Liu, Zhihong
Abstract: Although bortezomib has reported efficacy in light chain (AL) amyloidosis, the role of bortezomib in combination with dexamethasone (BD) as the first-line treatment for patients with AL amyloidosis has not been determined. We analyzed the outcomes of 72 consecutive unselected patients, which received primary therapy with BD in a single center. The patients were newly diagnosed with AL amyloidosis with renal (100%), cardiac (72%), hepatic (19%) or nervous system (10%) involvement and underwent a median of 2 (1–6) cycles of BD treatment. A hematologic response was achieved in 75% of the patients within a median period of 2 months, and 45% of those patients achieved a complete response. A renal response was achieved in 50% and 60% of patients at 1 year and 2 years, respectively, and a cardiac response was achieved in 40% and 46% of patients at 1 year and 2 years, respectively. After a median follow-up period of 24 months, the median duration of progression free survival was 45 months, and the estimated overall survival rates at 12 and 24 months were 83% and 76%, respectively. Baseline Eastern Cooperative Oncology Group performance status and proteinuria were associated with overall survival. The BD regimen induced high rates of rapid hematologic and organ responses in AL amyloidosis patients.